Strengthening family-community synergy: Enhancing protection and well-being for women and children - Helen Dian Fridayani; Muhammad Eko Atmojo; Nur Fitri Mutmainah; Habliy Mawaddah; Sindy Widyasari (University of Merdeka Malang, 2025)
The protection and well-being of women and children are essential pillars for fostering a safe, and resilient society. This community service initiative focuses on enhancing the safety and support systems for women and children in ‘Aisiyah organization Caturharjo, Sleman, by integrating family and community efforts. Through a participatory approach, the program emphasizes awareness-raising, and collaborative strategies to empower local stakeholders and promote a culture of shared responsibility. The initiative underscores the critical roles of family units, community organizations, and local leadership in preventing violence, ensuring access to essential services, and advocating for gender-sensitive and child-friendly policies. Engaging families and communities in dialogue and action, the program seeks to address systemic challenges and create a protective environment for vulnerable groups. Findings from the initiative reveal that the synergy between family and community efforts significantly contributes to sustainable protection measures and strengthens social resilience. The success of this initiative highlights the importance of inclusive, community-driven approaches in safeguarding women and children, offering valuable insights for replication in other regions. This community service effort not only addresses immediate safety concerns but also lays the foundation for long-term social change, demonstrating the transformative potential of collective action in building safer and more equitable communities.